Fungal colonization patterns and enzymatic activities of peatland ericaceous plants following long-term nutrient addition. (August 2020) - Kiheri, Heikki; Velmala, Sannakajsa; Pennanen, Taina; Timonen, Sari; Sietiö, Outi-Maaria; Fritze, Hannu; Heinonsalo, Jussi; van Dijk, Netty; Dise, Nancy; Larmola, Tuula
Abstract: Northern peatlands are often dominated by ericaceous shrub species which rely on ericoid mycorrhizal fungi (ERM) for access to organic sources of nutrients, such as nitrogen (N) and phosphorus (P), and host abundant dark septate endophytes (DSE). Relationships between hosts and fungal symbionts may change during deposition of anthropogenic N and P. We studied the long-term effects of N and P addition on two ericaceous shrubs, Calluna vulgaris and Erica tetralix, at Whim Bog, Scotland by analyzing fungal colonization of roots, enzymatic activity, and fungal species composition. Unexpectedly, the frequency of typical ERM intracellular colonization did not change while the occurrence of ERM hyphae tended to increase and DSE hyphae to decrease. Our findings indicate that altered nutrient limitations shift root associated fungal colonization patterns as well as affect ericaceous root enzyme activity and thereby decomposition potential. Reduction of recalcitrant fungal biomass in melanized DSE may have implications for peatland C sequestration under nutrient addition. Highlights: Long-term effects of N/NP on ericaceous root fungal colonization & enzymatic activity. ERM intracellular colonization unchanged, ERM hyphae increased & DSE hyphae decreased. Loss of recalcitrant fungal biomass in melanized DSE may reduce peatland C sink. Nitrate reduced C. vulgaris root enzyme activity, suggests host/symbiont sensitivity.